Pengaruh ukuran perusahaan, persediaan, harga pokok penjualan dan laba sebelum pajak terhadap pemilihan metode penilaian persediaan pada perusahaan manufaktur di bei - Nike Demos; Yana Ulfah; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Nike Demos, 2018. The Influence of Firm Size, Inventory,  Cost of Goods Sold and Earning Before Tax to Selection of Inventory Valuation Method on Manufacturing Companies in Indonesia Stock Exchange. Under guindance of Hj. Yana Ulfah and Indra Suyoto Kurniawan.This study aims to determine the effect of Firm Size, Inventory,  Cost of Goods Sold and Earning Before Tax to Selection of Inventory Valuation Method on Manufacturing Companies in Indonesia Stock Exchange (BEI). Variables used in this research is firm size, Inventory,  Cost of Goods Sold and Earning Before Tax as an independent variable and the method of inventory valuation as the dependent variable. Source of data used in the form of financial statements for 2013-2016 in order to obtain the amount of data as much as 100 data. Technique  data analysis using logistic regression.The survey result revealed that the firm size, Inventory,  Cost of Goods Sold and Earning Before Tax had a unsignificant influence on the selection method of inventory valuation on companies in the stock exchanges of Indonesia